2003
DOI: 10.1002/adma.200305228
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Electroluminescent Light‐Emitting Devices Based on Ethyne‐Bridged Porphyrin Fluorophores

Abstract: For the emitters following the Fowler±Nordheim (FN) theory, the plot of ln(J/E 2 ) versus E ±1 gives a straight line and its slope, ± (Bu 3/2 /b), determines the FN enhancement factor b, where E is the applied field, u is the work function, and B is a constant. The inset in Figure 5 displays the corresponding FN plot at a separation of 150 lm, showing a linear relationship and revealing that electron emission from the tips of the nanowires follows FN behavior. Here, we define the turn-on field and the threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 31 publications
2
60
0
1
Order By: Relevance
“…To this end, we took advantage of our mature experience in the synthesis of BODIPYporphyrin dyads and their implementation in solar cells [16][17][18][19] to trapping process at the porphyrin, (ii) there is an almost quantitative ET process from the BODIPY to the porphyrin, (iii) there is a lack of phase separation between both components in thin films as they are linked, and (iv) porphyrins are considered as one of the best candidates for developing narrow emission deepred OLEDs. 2,[20][21][22][23][24][25][26][27] On the other hand, LECs are ideal devices to demonstrate our concept, as they are single layer devices based on a single active component, allowing to settle clear relationships between molecular design and device performance. [8][9][10] In addition, this work provides, to the best of our knowledge, the first example of using this family of dyads in lighting schemes, demonstrating the benefits that state from their unique features.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we took advantage of our mature experience in the synthesis of BODIPYporphyrin dyads and their implementation in solar cells [16][17][18][19] to trapping process at the porphyrin, (ii) there is an almost quantitative ET process from the BODIPY to the porphyrin, (iii) there is a lack of phase separation between both components in thin films as they are linked, and (iv) porphyrins are considered as one of the best candidates for developing narrow emission deepred OLEDs. 2,[20][21][22][23][24][25][26][27] On the other hand, LECs are ideal devices to demonstrate our concept, as they are single layer devices based on a single active component, allowing to settle clear relationships between molecular design and device performance. [8][9][10] In addition, this work provides, to the best of our knowledge, the first example of using this family of dyads in lighting schemes, demonstrating the benefits that state from their unique features.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] This field is mainly driven by their ease of modification to enhance light-harvesting and photoluminescence (PL) properties based on an efficient energy and/or electron transfer process from moieties attached at the periphery to the porphyrin core.This feature of dyad-like porphyrins is of utmost relevance for lighting schemes, since it could open a new avenue to decouple charge transport and emission processes by only using one active compound. This is more critical in light-emitting electrochemical cells (LECs) than in OLEDs, in which the charge transport is not performed by the emitter, but by a multilayered device architecture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these porphyrin arrays show very weak ground-state electronic interactions between the porphyrin units. Various linear types of meso-to meso acetyleneand butadiyne-bridged multiporphyrins have also been reported and their photo physical and electrochemical properties have been determined [36][37][38]. In contrast to the arene-bridged porphyrin arrays, these types of multiporphyrins exhibit strong ground-and excitedstate interporphyrin electronic coupling.…”
Section: Multiporphyrins As Chemical Models For Photosynthesismentioning
confidence: 99%
“…In the covalently linked porphyrin arrays, a variety of linkages such as ethyne [36,37], polyyne [38][39][40], ethylene [41], alkane [42,43] and aromatic entities [44][45][46] have been used to bridge the individual porphyrins. Lindsey et al have reported the synthesis of numerous phenylene-and diphenyl ethynyl-bridged multiporphyrins for mimicking the biological light-harvesting antenna systems and their photo physical properties have been studied [46][47][48].…”
Section: Multiporphyrins As Chemical Models For Photosynthesismentioning
confidence: 99%